Hyperdiploidy is less frequent in AL amyloidosis compared with monoclonal gammopathy of undetermined significance and inversely associated with translocation t(11;14) - Bochtler, Tilmann; Hegenbart, Ute; Heiß, Christiane; Benner, Axel; Moos, Marion; Seckinger, Anja; Pschowski-Zuck, Stephanie; Kirn, Désirée; Neben, Kai; Bartram, Claus R.; Ho, Anthony Dick; Goldschmidt, Hartmut; et al. (Blood, 2011)
In multiple myeloma (MM) pathogenesis, hyperdiploidy and nonhyperdiploidy are recognized as 2 major cytogenetic pathways. Here, we assessed the role of hyperdiploidy in 426 patients with monoclonal plasma cell disorders, among them 246 patients with AL amyloidosis (AL), by interphase fluorescence in situ hybridization. Hyperdiploidy was defined by a well-established score requiring trisomies for at least 2 of the 3 chromosomes 5, 9, and 15. The hyperdiploidy frequency in AL was a mere 11% compared with 30% in monoclonal gammopathy of undetermined significance (P < .001) and 46% in AL with concomitant MM I (P < .001). Overall, hyperdiploidy was associated with an intact immunoglobulin, κ light chain restriction, higher age, and bone marrow plasmacytosis, but was unrelated to the organ involvement pattern in AL. Clustering of 6 major cytogenetic aberrations in AL by an oncogenetic tree model showed that hyperdiploidy and t(11;14) were almost mutually exclusive, whereas gain of 1q21 favored hyperdiploidy. Deletion 13q14 and secondary IgH translocations were equally distributed between ploidy groups. We conclude that the interphase fluorescence in situ hybridization-based hyperdiploidy score is also a feasible tool to delineate hyperdiploid patients in early-stage monoclonal gammopathies and that the cytogenetic pathogenetic concepts developed in MM are transferable to AL.